2012
DOI: 10.1063/1.4705525
|View full text |Cite
|
Sign up to set email alerts
|

Interface tension of silica hydroxylated nanoparticle with brine: A combined experimental and molecular dynamics study

Abstract: We have used molecular dynamics simulations to calculate the interfacial tension of hydroxylated SiO(2) nanoparticles under different temperatures and solutions (helium and brine with monovalent and divalent salts). In order to benchmark the atomistic model, quartz SiO(2) interfacial tension was measured based on inverse gas chromatography under He atmosphere. The experimental interfacial tension values for quartz were found between 0.512 and 0.617 N/m. Our calculated results for the interfacial tension of sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…13 It was found that the different propensity of the ions to distribute on the NPs surface affects the interfacial tension. Ranatunga et al simulated NPs and non-ionic surfactants at the oil-water interface using molecular dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…13 It was found that the different propensity of the ions to distribute on the NPs surface affects the interfacial tension. Ranatunga et al simulated NPs and non-ionic surfactants at the oil-water interface using molecular dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the quartz surfaces used for the calculations were generated by cleaving the bulk quartz material to give (0 0 0 1) surfaces with under-coordinated surface species, e.g. singly coordinated oxygen and three-coordinated silicon atoms following our previous work [35]. Termination of the dangling bonds in surface Si and O atoms with hydroxy groups and protons, respectively, resulted in the formation of the surface silanol groups.…”
Section: Methodsmentioning
confidence: 99%
“…Â was calculated using Eq. (3)[35][36][37], where H is the maximum droplet height and R the radius of the circle (dashed line) as indicated in the images. (For interpretation of the references to color in this figure legend, the reader is referred to the web version of this article.)…”
mentioning
confidence: 99%
“…We have obtained the pressure tensor for each atom individually according to the method described by Thompson et al 16 . From the obtained pressure tensor, after its transformation to cylindrical coordinates (as described by Kim et al 22 and Wang et al 23 ), we were able to obtain the interfacial tensions with the Irving-Kirkwood method 24 , as described by de Lara et al 25 . The following equation was used to calculate the interfacial tensions: where γ is the interfacial tension and p ( r ) is the radial component of the pressure tensor.…”
Section: Methodsmentioning
confidence: 99%